SCALED DYNAMIC TESTING ON LIGHTWEIGHT CONCRETE FOR WAVE SUPPRESSING SYSTEM - MOHD NOR, MOHD ABSHAR (Universiti Teknologi Petronas, 2006)
The Wave Suppression System (WSS) invented by Mohammad Firdaus Hashim has shown promising results, and UTP is keen to further develop the invention to the point of making it commercially usable and viable. 'This project serves as part of UTP 's effort to make the WSS workable, viable and durable for commercial use. The project focuses on trying to determine the durability of the ALC used in the WSS by conducting a series of tests which best simulates the dynamic wave forces to a scaled model. There will be two main test; maximum strength and cyclic loading resistance. The former results are significant in two ways; they provide a reference load to the second tests and providing maximum strength value for WSS designers to relate with the retnrn period of certain wave heights. The return period of a wave height that is equal to the WSS maximum strength shall serve as the lifespan of the WSS in terms of years. If the maximum strength is equivalent to a 10 m wave height, and the targeted coast area has a hypothetical 20 years return period for I 0 m waves, the WSS will theoretically last for 20 years. However, even low wave heights, which equal low forces, which continuously hit the WSS of long period of time may cause the WSS to fail due to fatigue crack propagation. This is why the second test is employed to determine its resistance for cyclic loading. The test will give the maximum number of cycles the WSS can withstand before failure at a variety of frequencies arbitrarily set to the most common wave periods. The load shall be varied in terms of percentage of the maximum load. It must be noted that in order to compare the results with the aetna! wave forces, dynamic similarity must be achieved as close as possible between the intended full scale prototype and the scaled model. The dynamic similarity is reasonably achievedby correcting the results with the appropriate scale factor. The corrected results will then be used as a basis for comparison with actual wave periods. The experiments results expose the ALC weakness, which is low maximum strength and low resistance to cyclic loading. Even under the most favourable coastal circumstances the ALC will struggle to last for more than 6 months.